Rancang Bangun Mobile Commerce di Lamandau Store Berbasis Android berdasarkan User Centered Design (UCD) - Tadonny Vani; Rahmat Hidayat; Arnoldus Yansen Friska Danar Yudhistira (STMIK Budi Darma, 2021)
Lamandau Store is a place for marketing and selling products that produced by Micro, Small and Medium Entrepreneurs named Usaha Mikro Kecil Menengah (UMKM) and Small Medium Industry products or Industri Kecil Menengah (IKM) in Lamandau Regency. The marketing and sales system at Lamandau Store has been manual which is costumers come to the store. This has not attracted enough consumers, resulting in lower levels of marketing and sales. This study aims to produce an Android-based mobile commerce application that can be used to support the marketing and sales process at the Lamandau Store. The research was conducted in several stages, namely the Data Collection Stage, the System Design Stage and the Report Writing Stage. The system design stage was developed based on the User Centered Design (UCD) method. The results show that a mobile commerce application is in accordance with user needs and has been presented as a new innovation at the Lamandau Store.